The Efficacy of Supportive Peri-Implant Therapies in Preventing Peri-Implantitis and Implant Loss: a Systematic Review of the Literature - Ausra Ramanauskaite; Tellervo Tervonen (Stilus Optimus, 2016)
Objectives: To study the efficacy of supportive peri-implant therapies in preventing clinical and radiological signs of peri-implantitis and implant loss. Material and Methods: Longitudinal human studies, published between January 1, 2006, and February 1, 2016, were included based on an electronic search using MEDLINE and EMBASE databases and complemented by a manual search. Articles were included only if 1) they comprised a group of patients involved in/adhering to regular supportive peri-implant therapies (SPTs) and a control group without such therapies or with poor adherence to them, 2) the protocol of the SPTs was clearly described and 3) the outcome was indicated by means of clinical/radiological changes or implant loss. Results: After initially identifying a total of 710 titles and abstracts, 12 full text articles were selected for eligibility assessment. Seven studies, three prospective and four retrospective, fulfilled the inclusion criteria for this review. The frequency of recall visits varied between the studies from a minimum of one visit every three months to an individually tailored regimen. In all the studies a lack of SPTs or poor adherence to them resulted in significantly higher frequencies of sites with mucosal bleeding, deepened peri-implant pockets or alveolar bone loss. In line with the above, a lack of/poor adherence to SPTs was associated with higher implant loss. Conclusions: To prevent peri-implantitis, an individually tailored supportive programme based on patient motivation and re-instruction in oral hygiene measures combined with professional implant cleaning seem to be crucial.